Sex differential genetic effect of chromosome 9p21 on subclinical atherosclerosis. - Hsiu-Fen Lin (PLoS ONE, 2010)
BACKGROUND: Chromosome 9p21 has recently been shown to be a risk region for a broad range of vascular diseases. Since carotid intima-media thickness (IMT) and plaque are independent predictors for vascular diseases, the association between 9p21 and these two phenotypes was investigated. METHODOLOGY/PRINCIPAL FINDINGS: Carotid segment-specific IMT and plaques were obtained in 1083 stroke- and myocardial infarction-free volunteers. We tested the genotypes and haplotypes of key single nucleotide polymorphisms (SNPs) on chromosome 9p21 for the associations with carotid IMT and plaque. Multivariate permutation analyses demonstrated that carriers of the T allele of SNP rs1333040 were significantly associated with thicker common carotid artery (CCA) IMT (p=0.021) and internal carotid artery (ICA) IMT (p=0.033). The risk G allele of SNP rs2383207 was associated with ICA IMT (p=0.007). Carriers of the C allele of SNP rs1333049 were found to be significantly associated with thicker ICA IMT (p=0.010) and the greater risk for the presence of carotid plaque (OR=1.57 for heterozygous carriers; OR=1.75 for homozygous carriers). Haplotype analysis showed a global p value of 0.031 for ICA IMT and 0.115 for the presence of carotid plaque. Comparing with the other haplotypes, the risk TGC haplotype yielded an adjusted p value of 0.011 and 0.017 for thicker ICA IMT and the presence of carotid plaque respectively. Further analyzing the data separated by sex, the results were significant only in men but not in women. CONCLUSIONS: Chromosome 9p21 had a significant association with carotid atherosclerosis, especially ICA IMT. Furthermore, such genetic effect was in a gender-specific manner in the Han Chinese population.